THE EFFECTIVENESS OF INSTAGRAM CAPTIONS IN ENHACING STUDENTS’ WRITING - Nur Azizah (Adisam Publisher, 2024)
The aim of this research was to enhancing students’ writing skill in third semester by adding Instagram caption on the students’ process in teaching and learning. The design of this research was descriptive qualitative research to describe the effectiveness of Instagram captions to enhacing students’ writing skill in third semester of Tadris English language. The research was conducted as Sekolah Tinggi Agama Islam mempawah in academic year 2024-2025. It was selected by the researcher based on the backgound of the students knowledge in writing skill. In this research, the researchen found that the students face some difficulties in writing English text. In collecting data, the researcher used were observation and interview the students in third semester. The observation one class only. Most of the students in the classroom are eight students. Three students male and five students are female. The researcher found that the students still difficult to write in some sentencess especially make a caption in their status story in Instagram. The puppose of this research is to find out the effectiveness of Instagram caption in increasing students writing skill. Based on the explanation and result of the student’s write caption on Instagram, the researcher found that writing captions on Instagram is indeed effective in improving student’s writing skill.